Kombinasi Injeksi Triamsinolon Asetat Intralesi dan Propanolol Oral pada Kasus Hemangioma Kapiler Palpebra - Mardijas Efendi; Hendriati Hendriati; Ardizal Rahman; Muhammad Fadhil Rahmadiansyah (Jurnal Kesehatan Andalas, 2022)
Capillary hemangioma is a benign tumor developed from the abnormal proliferation of blood vessels. This tumor appears on eyelids and orbit. Around 75% of hemangioma resolves spontaneously in the first 4-5 years of life. Intervention is needed in hemangioma that obstructs the visual axis. It has been reported that a two-year-old girl came to Polyclinic with a mass on the left superior eyelid 1,5 years ago. At first, the left superior eyelid looked puffy, then developed slowly until it covered the left eye. On the examination of the left eye, visual acuity assessment was hard to perform. Mass in superior palpebral was 8mm x 8mm x 8mm, reddish colored (different with adjacent skin), consistency supple, mobile, painful (-), edema (+), horizontal palpebral fissure (FPH) 30 mm, vertical palpebral fissure (FPV) 0 mm. CT scan showed suspected hemangioma. The patient was diagnosed with capillary hemangioma and given an injection of triamcinolone acetate intralesional and oral propranolol under the supervision of a pediatrician. Significant clinical improvement was observed after 40 days of injection, where the mass was resolved completely. The FPV and FPH of the left eye had improved to 9 mm and 30 mm, respectively, with the patient finally able to follow the object. The combination of intralesional triamcinolone acetate and oral propranolol in this case is quite effective in providing complete resolution of capillary hemangioma.Keywords:  capillary hemangioma, triamcinolone acetate injection, propanolol